PENGUATAN KECERDASAN AKHLAK AKTUAL-PRODUKTIF ( Filsafat Etika dan Psikologi Moral) - Arfan, Surya; M, Amril; Dewi, Eva (Komunitas Manajemen Kompetitif, 2025)
Actual-productive moral intelligence is a form of moral intelligence that not only understands the values of goodness but is also capable of consistently and responsibly translating them into concrete actions in social life. In the context of education and character development, strengthening this intelligence is crucial to addressing the challenges of the modern era, marked by moral crises and the degradation of ethical values. An integrative approach combining ethical philosophy and moral psychology is considered effective for fostering moral character that is not only theoretically ideal but also productive in action. Moral intelligence must be developed through an approach that balances rational and emotional aspects to produce a whole and integrity-driven individual. The strengthening of students' morality must be carried out through contextual, reflective, and transformative learning strategies. Additionally, the importance of social and cultural support from the school environment in shaping productive morality that is internalized into daily habits cannot be overlooked. This study aims to examine the concepts, approaches, and strategies for strengthening actual-productive moral intelligence by analyzing the philosophical foundations of ethics and moral psychology theory, as well as proposing an integrative implementation model in the context of character education. The method used is a qualitative study with a descriptive-analytical approach through literature review. The results of the study indicate that the synergy between ethical philosophy (teleological and deontological) and moral psychology theory (such as the theory of moral development stages) provides a strong framework for fostering actual and productive moral intelligence in real life.